Sahara Occidental: Actores y dinámicas regionales en los orígenes del conflicto (1974-1979) - Inmaculada Cordero; Encarnación Lemus (Mélanges de la Casa de Velázquez, 2022)
During the decade of the 70s, a latent conflict spread in the Maghreb due to the decolonization of Western Sahara. The interests of the great powers had a lot to do with it. Although the interventions of some of the actors and observers have already been analysed, the dynamics of collaboration and mediation in the conflict in which surrounding countries engaged are barely known.This work analyses the positions and actions undertaken by Tunisia and Senegal which, in fact, intervened in this dispute, always following in France’s wake, holding, as a consequence, pro-Moroccan views. Notwithstanding, both tried to prevent a possible conflagration in the Maghreb in the presence of a conflict in which history and political interests converged.Behind them, both France and the United States, apparently neutral, promoted meetings and discussions with the aim of preventing direct armed confrontation between Morocco and Algeria.